2006
DOI: 10.1590/s1678-91992006000200009
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of propolis collected in different regions of Brazil

Abstract: ABSTRACT:The aim of this study was to investigate the antibacterial activity of propolis samples from Goiás, Paraná and São Paulo States, Brazil, and their flavonoids content. Ethanolic extracts of propolis (EEP) were prepared (30g of propolis in 70% ethanol), and the microorganisms Staphylococcus aureus and Escherichia coli were tested. The methodology employed was agar diffusion using filter paper discs. Ampicillin and tetracycline were used as controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 14 publications
6
45
0
14
Order By: Relevance
“…The mechanisms of action are not fully understood, the most possible explanation for the low sensitivity of Gram-negative bacteria is that their outer membrane (phospholipids, proteins, and lipopolysaccharides structure) inhibits and/or retards the penetration of propolis (TegoS et al, 2002). These results are in agreement with previous reports (GonSALeS et al, 2006). Moreover, it has been reported that propolis exhibits bacteriostatic activity against different bacterial strains and can be bactericidal in a high concentration (MirzoevA et al, 1997).…”
Section: Antimicrobial Activity Of Eepssupporting
confidence: 91%
“…The mechanisms of action are not fully understood, the most possible explanation for the low sensitivity of Gram-negative bacteria is that their outer membrane (phospholipids, proteins, and lipopolysaccharides structure) inhibits and/or retards the penetration of propolis (TegoS et al, 2002). These results are in agreement with previous reports (GonSALeS et al, 2006). Moreover, it has been reported that propolis exhibits bacteriostatic activity against different bacterial strains and can be bactericidal in a high concentration (MirzoevA et al, 1997).…”
Section: Antimicrobial Activity Of Eepssupporting
confidence: 91%
“…In addition, propolis is known to be a health food that presents antibacterial, antioxidative, immunomodulatory, antifungal, antiviral, antiprotozoal, antiinflammatory and antitumor activities (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Bosio et al (13) Though the antibacterial activity of propolis essential oil from Paraná and Piauí states has been reported, the literature on the antimicrobial activity of this oil from Rio de Janeiro State is scarce (17,21).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, of all 161 bacterial isolates (81 grampositive and 80 gram-negative), belonging to the Universidade Federal de Santa Maria -RS Bacteriology Laboratory, 92.6% of gram-positive isolates were found to be sensitive to propolis, whereas only 42.5% of gram-negative bacteria were sensitive to the propolis extract (5,27) .…”
Section: Resultsmentioning
confidence: 98%
“…Other studies emphasize the influence that the chemical composition of propolis has on its antimicrobial activity, warning that flavonoid concentration changes according to the flora and seasonal conditions of the region where collection was conducted (3,7,27,35) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation